National Resilience in the Study of Islamic Boarding Schools: A Literature Review - Gilang Kurnia Pamungkas; Muhammad Bisri; Maftuch (Universitas Merdeka Malang, 2025)
Islamic boarding schools (pesantren) play a crucial role in national resilience in Indonesia, given that they are religious educational institutions that not only instill Islamic values but also serve as strategic partners for the state in strengthening tolerance, inclusiveness, and ideological stability in society. In the context of public policy, Islamic boarding schools contribute to strengthening the national security system through character education, religious moderation, and fostering national awareness aligned with the nation's ideological and social resilience agenda. Therefore, this study aims to evaluate international publication trends on Islamic boarding schools and national resilience using the Scopus database through bibliometric analysis from 2009 to 2025. Data visualization and analysis were performed using Bibliometric and VOSviewer. The results show that discussions on Islamic boarding schools within the framework of national resilience frequently appear in educational journals. Furthermore, the relationship between Islamic boarding schools and national resilience appears to have strong relevance through themes such as multicultural education, religious moderation, and the social role of Islamic boarding schools in supporting the national security policy agenda. These findings are expected to contribute to the novelty of studies on Islamic boarding schools and national resilience, particularly in the context of strengthening the basis of public policy